Genome-wide identification of Kip-related protein (KRP) gene family members in eggplant and the function of SmKRP3 under salt stress - Lei Shen; Shixin Yang; Xin Xia; Wenfeng Nie; Xu Yang (Vegetable Research)
Kip-related proteins (KRPs) are essential to cell division throughout their whole process of growth and development. Research on KRPs and their roles has mostly focused on Arabidopsis thaliana. Nonetheless, details on the structure and functions of KRP gene family members in eggplant are still unclear. In this study, we have discovered and analyzed five KRP genes in the eggplant HQ-1315 genome. Our investigation focused on determining their chromosomal position, collinearity, gene structure, conserved motif, and domain, as well as cis-element. The expression levels of all KRP genes were decreased by salt and dehydration stress, except SmKRP3. The expression of SmKRP3 was significantly increased by salt stress. Transient expression assay revealed that all of the eggplant KRP proteins are located in the nucleus of epidermic cells of Nicotiana benthamiana leaves. Silencing of SmKRP3 increased the sensitivity of eggplant to salt stress. This was accompanied by a significant decrease in the expression of salt stress marker genes SmGSTU10, SmNCED1, SmDHN1, and SmDHNX1. An apparent decrease in the activity of the enzymes ascorbate peroxidase (APX) and catalase (CAT). Our findings show that SmKRP3 has a positive role in salt stress, shedding fresh light on the complete information of the KRP gene family members in eggplants.